An integrated model to evaluate the effects of cloud computing services on SMEs performance - Ruzaini, Abdullah Arshah; Mohammed Abdullah, Ali Al-Sharafi (2018)
In Malaysia 97.3% business establishments, 65.5% total employment and 36.3% GDP are SMEs. SMEs that adopt Cloud Computing Services (CCS) can receive value over time if they continue to use the CCS solution after implementation. The assessment of the factors that affect SMEs to continuous use CCS, not a simple task due to lack of adequate methods and tools for such task. The model designed to help organizations maximize the value of CCS by increasing knowledge about the extent to which various factors affect the continuous use of CCS. The developed model will help CCS providers to increase their competitive edge and will help SMEs to increase their financial and non-financial performance.